The playhouse - Ground, Saunder V. (Columbia, S.C. : South Caroline ETV, 1990)
The Playhouse is a six-part videocassette series with accompaning Curriculum Guide designed to aid in the prevention of alcohol drug abuse among preschool
A South Carolina ETV Production
Keywords: Play groups -- United States; Play schools -- United States